Profiling DNA supercoiling domains in vivo - Corless, Samuel (Genom Data, 2014)
Transitions in DNA structure have the capacity to regulate genes, but have been poorly characterised in eukaryotes due to a lack of appropriate techniques. One important example is DNA supercoiling, which can directly regulate transcription initiation, elongation and coordinated expression of neighbouring genes. DNA supercoiling is the over- or under-winding of the DNA double helix, which occurs as a consequence of polymerase activity and is modulated by topoisomerase activity [5]. To map the distribution of DNA supercoiling in nuclei, we developed biotinylated 4,5,8-trimethylpsoralen (bTMP) pull-down to preferentially enrich for under-wound DNA. Here we describe in detail the experimental design, quality controls and analyses associated with the study by Naughton et al. [13] that characterised for the first time the large-scale distribution of DNA supercoiling in human cells (GEO: GSE43488 and GSE43450GSE43488GSE43450).